2019
DOI: 10.1080/11035897.2019.1655790
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrate remains and conodonts in the upper Silurian Hamra and Sundre formations of Gotland, Sweden

Abstract: A long history of geological research on the island of Gotland, Sweden, has resulted in a detailed biostratigraphy based on conodonts for the Gotland sedimentary succession, but the relation between the Hamra and Sundre formations, the youngest strata on southern Gotland, has remained poorly resolved. These formations have also remained relatively poorly described in terms of vertebrates compared to other parts of the succession. A survey of museum collections and newly sampled material reveal that the taxonom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…crispa has also been found in sample G72-17CB from Glasskär 1 (probably Burgen Oolite Formation). This species is also known from earlier occurrences in the Baltic area (Viira & Aldridge, 1998;Bremer et al, 2020), although Märss and Männik (2013) suggested that these may represent specific morphologies of Oz. snajdri and considered them Oz.…”
Section: Conodont Biostratigraphy and Diversitymentioning
confidence: 82%
See 3 more Smart Citations
“…crispa has also been found in sample G72-17CB from Glasskär 1 (probably Burgen Oolite Formation). This species is also known from earlier occurrences in the Baltic area (Viira & Aldridge, 1998;Bremer et al, 2020), although Märss and Männik (2013) suggested that these may represent specific morphologies of Oz. snajdri and considered them Oz.…”
Section: Conodont Biostratigraphy and Diversitymentioning
confidence: 82%
“…sculptilis (Fredholm, 1989) and poracanthodid acanthodians (Fredholm, 1989;Eriksson et al, 2009) from Burgen outlier indicate a late-, rather than mid-Ludlow age of these samples (see Märss and Männik, 2013). Indeed, these taxa are more readily found in younger strata on Gotland (Bremer et al, 2020). Furthermore, the samples from Burgen outlier lack the thelodonts Thelodus carinatus Pander, 1856 and Phlebolepis elegans Pander, 1856 that are typical for faunas found in older strata on Gotland (e.g., Fredholm, 1989;Eriksson et al 2009).…”
Section: Vertebrate Biostratigraphy and Diversitymentioning
confidence: 96%
See 2 more Smart Citations
“…3C-D) as the neotype for Gomphonchus volborthi. The geographical and stratigraphic distribution of the species is as follows: upper Silurian, lower Přidoli, Ludlow Bone Bed; Welsh Borderland, U.K. (Vergoossen 1999a); Ludlow to lower Přidoli, ?När to Sundre formations, Gotland, Sweden (Bremer et al 2019b); Ludlow to lower Přidoli, Öved Sandstone Formation, southern Sweden; upper Ludlow, Uduvere Beds of the Paadla RS and Tahula Beds of the Kuressaare RS, Estonia; uppermost Ludlow/lower Přidoli, Winnica Formation, Holy Cross Mountains, Poland (Bremer et al 2018); upper Silurian, lower Přidoli, erratics, the Netherlands (Vergoossen 1999c(Vergoossen , 2002; possibly Ludlow or Přidoli, reworked deposit in Quaternary gravels, Mazury Quarry, near Minsk, Belarus (Plax 2019). (Lehman, 1937) Radioporacanthodes biblicus was regarded by Gross (1947) as a junior synonym of Poracanthodes porosus Brotzen, 1934(now Radioporacanthodes porosus, see Vergoossen 1997), but the species was resurrected by Vergoossen (2002).…”
Section: Gomphonchus Volborthi (Rohon 1893)mentioning
confidence: 99%